ANALISIS PENDAPATAN DAN KESEJAHTERAAN PETANI KARET DI DESA SARI MULYA KABUPATEN TANAH BUMBU - FITRIYANA FITRIYANA; RIZALI RIZALI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted with the aim of analyzing the income and welfare of rubber farmers in Sari Mulya village, Sungai Loban District, Tanah Bumbu Regency. The number of respondents in this study were 67 samples. And this research uses descriptive quantitative method The results of this study indicate that the average income of rubber farmers in the village of Sari Mulya sub-district Sungai Loban Regency Tanah Bumbu is Rp.3,761,726. and for the level of prosperity the rubber farmers in the village of Sari Mulya belong to the prosperous farmers.Keywords: Income, Welfare